Scientific developments in understanding food allergy prevention, diagnosis, and treatment - Hund, Shirin Karimi; Sampath, Vanitha; Zhou, Xiaoying; Thai, Bryan; Desai, Khushi; Nadeau, Kari C. (Frontiers in immunology, 2025)
Food allergies (FAs) are adverse immune reactions to normally innocuous foods. Their prevalence has been increasing in recent decades. They can be IgE-mediated, non-IgE mediated, or mixed. Of these, the mechanisms underlying IgE-mediated FA are the best understood and this has assisted in the development of therapeutics. Currently there are two approved drugs for the treatment of FA, Palforzia and Omalizumab. Palfornia is a characterized peanut product used as immunotherapy for peanut allergy. Immunotherapy, involves exposure of the patient to small but increasing doses of the allergen and slowly builds immune tolerance to the allergen and increases a patient’s allergic threshold. Omalizumab, a biologic, is an anti-IgE antibody which binds to IgE and prevents release of proinflammatory allergenic mediators on exposure to allergen. Other biologics, investigational vaccines, nanoparticles, Janus Kinase and Bruton’s tyrosine kinase inhibitors, or DARPins are also being evaluated as potential therapeutics. Oral food challenges (OFC) are the gold standard for the diagnosis for FA. However, they are time-consuming and involve risk of anaphylaxis; therefore, alternative diagnostic methods are being evaluated. This review will discuss how the immune system mediates an allergic response to specific foods, as well as FA risk factors, diagnosis, prevention, and treatments for FA.